Women's Rights in Marriage Perspective Maqasid Al-Usrah Jamaludin Athiyah - Rohman, Muhammad Fadlil; Sa’adah, Sri Lumatus; Wahab, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research is motivated by the large number of divorces caused by women's rights not being fulfilled in marriage, and the presence of the Court to seek justice. The judge is the person who examines, adjudicates, and decides cases with the judge's considerations which must touch the image of the law. This research is interesting because it looks at the judge's considerations from the perspective of maqasid al-usrah Jamaludin Athiyah. This research is quantitative (normative law) using a statutory approach using a study of judges' decisions in searching for normative legal research, in this case, decision number 1084/Pdt.G/2023/PA.Bdw as the research object. This research concludes 1) that the development of special sharia maqasid, one of which is maqasid al-usrah, maqasid al-usrah itself has been used in several contemporary maqasidiyyun writings. Jamaludin Athiyah is one of the figures who use the term maqasid al-shari'ah fi ma yakhussu al-usrah. Jamaludin Athiyah's view in his ideas is more encouraging in efforts to protect human rights both in the realm of individuals, families, people, and humanity. This can be resolved in the realm of policy. 2) In case number 1084/Pdt.G/2023/PA.Bdw the reason is that the wife experienced domestic violence and the husband's lack of responsibility in providing a living. Then, in the judge's consideration, the judge considered that the family could no longer be maintained, so the judge had a legal basis, namely "Avoiding mafsadat is prioritized to maintain the benefit." When viewed from the perspective of maqasid al-usrah, the judge's considerations fall into the individual realm, to protect the wife's soul and mind, and then into the family realm. Maintaining family financial institutions means that husbands are obliged to provide support for their wives and children.